The concept of God: From the lens of students of integrated Islamic elementary schools - Reni Susanti; Ikhwanisifa Ikhwanisifa (Universitas Ahmad Dahlan, 2020)
Children at elementary schools have been able to develop their logical thinking and the ability to understand symbols and fundamental principles, yet still in a concrete fashion. Religion, however, introduces the concept of God, which is quite an abstract concept. Therefore, a learning method that can help children to develop their understanding of God is required. This research aimed to identify the conception of God on children enrolled in Integrated Islamic schools (SIT). The study used qualitative method with the indigenous psychology approach. The study collected data from 200 students at Grade Six from Integrated Islamic elementary schools in Pekanbaru. The data was processed using thematic analysis based on the conception of God in Islamic tradition. The results showed that the majority of the respondents (97.73%) described their conception of God with their understanding of God as the Creator (tawhid al-rububiyya) involving the perfection of God, the willfulness of God, and the existence of God. The implementation of the understanding of God in daily life (tawhid al-uluhiyya) is then applied through prayers, compliance to religious rules, and submission toward God's commands. These results suggest that respondents comprehend the concept of God and implement such understanding through their daily activities